1999
DOI: 10.1172/jci7319
|View full text |Cite
|
Sign up to set email alerts
|

Tsc2+/– mice develop tumors in multiple sites that express gelsolin and are influenced by genetic background

Abstract: Tuberous sclerosis (TSC) is an autosomal dominant genetic disorder in which benign hamartomas develop in multiple organs, caused by mutations in either TSC1 or TSC2. We developed a murine model of Tsc2 disease using a gene targeting approach. Tsc2-null embryos die at embryonic days 9.5-12.5 from hepatic hypoplasia. Tsc2 heterozygotes display 100% incidence of multiple bilateral renal cystadenomas, 50% incidence of liver hemangiomas, and 32% incidence of lung adenomas by 15 months of age. Progression to renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
379
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 356 publications
(410 citation statements)
references
References 26 publications
29
379
1
1
Order By: Relevance
“…The Eker rat, which carries a germline mutation in the rat TSC2 homologue, develops renal cysts and carcinomas with an autosomal-dominant pattern of inheritance (27,28). Two groups have developed mice with targeted inactivation of TSC2 (29,30). Both mouse models develop renal carcinomas and cysts similar to those of the Eker rat.…”
Section: Discussionmentioning
confidence: 99%
“…The Eker rat, which carries a germline mutation in the rat TSC2 homologue, develops renal cysts and carcinomas with an autosomal-dominant pattern of inheritance (27,28). Two groups have developed mice with targeted inactivation of TSC2 (29,30). Both mouse models develop renal carcinomas and cysts similar to those of the Eker rat.…”
Section: Discussionmentioning
confidence: 99%
“…In other organs such as the adrenals, brain, pituitary, small and large intestine, stomach, testis, and retina, the distributions of the two proteins overlapped, but were not identical. Tsc1 and Tsc2 are the genes responsible for human TSC and renal carcinogenesis in rodents (European chromosome 16 tuberous sclerosis consortium, 1993; Kobayashi et al, 1995Kobayashi et al, , 1999Onda et al, 1999;van Slegtenhorst et al, 1997), and binding between two proteins has been reported as the possible cooperative function (Plank et al, 1998;van Slegtenhorst et al, 1998). In terms of cell type specificity, the overlapped, but not identical expression profile between Tsc1 and Tsc2 suggest that Tsc1 protein does not always associate with Tsc2 in all organs and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…While the hamartomas can grow in size to cause serious medical problems, they rarely become malignant; for example, only B2% of TSC patients develop malignant tumors, which tend to occur in the kidney (reviewed in Kwiatkowski, 2003). In mice, homozygous inactivation of either TSC1 or TSC2 results in embryonic lethality, while heterozygous inactivation predisposes the animals to tumorigenesis, consistent with these proteins providing tumor suppressor function in vivo (Onda et al, 1999;Kobayashi et al, 1999Kobayashi et al, , 2001; and reviewed in Kwiatkowski, 2003).…”
Section: Tsc1/2 a Novel Negative Regulator Of Tormentioning
confidence: 99%